Forced Preservation: Electronic Evidence and the Business Records Hearsay Exception - Dore, Michael H. (Science and Technology Law Review, 2009)
To be admissible under the hearsay rule’s business records exception set out in Federal Rule of Evidence 803(6), the record in question must have been “kept in the ordinary course of a regularly conducted business activity.” Many electronic records, however, remain in a company’s files only because the company had a duty to preserve them once it reasonably anticipated litigation or a government subpoena. The company otherwise typically would have deleted those electronically stored data in the regular operation of its business to make room on its burdened servers. This Article argues that such presumptive deletion undermines the trustworthiness and reliability of a business record, and thus the rationale of Rule 803(6). Courts should therefore focus on the unique elements of the creation and preservation of electronic evidence, and consider whether a company truly kept the record at issue in the course of business, or simply because a duty to preserve required it.